Assessment of health system readiness for routine maternal and newborn health services in Nepal: Analysis of a nationally representative health facility survey, 2015. - Resham B Khatri; Yibeltal Assefa; Jo Durham (Public Library of Science (PLoS), 2022)
Access to and utilisation of routine maternal and newborn health (MNH) services, such as antenatal care (ANC), and perinatal services, has increased over the last two decades in Nepal. The availability, delivery, and utilisation of quality health services during routine MNH visits can significantly impact the survival of mothers and newborns. Capacity of health facility is critical for the delivery of quality health services. However, little is known about health system readiness (structural quality) of health facilities for routine MNH services and associated determinants in Nepal. Data were derived from the Nepal Health Facility Survey (NHFS) 2015. Total of 901 health facilities were assessed for structural quality of ANC services, and 454 health facilities were assessed for perinatal services. Adapting the World Health Organization's Service Availability and Readiness Assessment manual, we estimated structural quality scores of health facilities for MNH services based on the availability and readiness of related subdomain-specific items. Several health facility-level characteristics were considered as independent variables. Logistic regression analyses were conducted, and the odds ratio (OR) was reported with 95% confidence intervals (CIs). The significance level was set at p-value of <0.05. The mean score of the structural quality of health facilities for ANC, and perinatal services was 0.62, and 0.67, respectively. The average score for the availability of staff (e.g., training) and guidelines-related items in health facilities was the lowest (0.37) compared to other four subdomains. The odds of optimal structural quality of health facilities for ANC services were higher in private health facilities (adjusted odds ratio (aOR) = 2.65, 95% CI: 1.48, 4.74), and health facilities supervised by higher authority (aOR = 1.96; CI: 1.22, 3.13) while peripheral health facilities had lower odds (aOR = 0.13; CI: 0.09, 0.18) compared to their reference groups. Private facilities were more likely (aOR = 1.69; CI:1.25, 3.40) to have optimal structural quality for perinatal services. Health facilities of Karnali (aOR = 0.29; CI: 0.09, 0.99) and peripheral areas had less likelihood (aOR = 0.16; CI: 0.10, 0.27) to have optimal structural quality for perinatal services. Provincial and local governments should focus on improving the health system readiness in peripheral and public facilities to deliver quality MNH services. Provision of trained staff and guidelines, and supply of laboratory equipment in health facilities could potentially equip facilities for optimal quality health services delivery. In addition, supervision of health staff and facilities and onsite coaching at peripheral areas from higher-level authorities could improve the health management functions and technical capacity for delivering quality MNH services. Local governments can prioritise inputs, including providing a trained workforce, supplying equipment for laboratory services, and essential medicine to improve the quality of MNH services in their catchment.